2018
DOI: 10.3928/23258160-20180501-07
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1, Open-Label, Dose-Escalation Trial to Investigate Safety and Tolerability of Single Intravitreous Injections of ICON-1 Targeting Tissue Factor in Wet AMD

Abstract: Intravitreous administration of ICON-1 in single doses up to 300 μg in eyes with neovascular AMD was safe and well-tolerated. [Ophthalmic Surg Lasers Imaging Retina. 2018;49:336-345.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Basically, it consists of two identical chains of proteins: human Factor VII (fVII) as the targeting domain and human immunoglobulin G1 Fc as the effector domain, functioning as binding to pathological vessels overexpressing tissue factor ( Bora et al, 2003 ; Tezel et al, 2007 ). Although intravitreous administration of a single 0.3 mg dose of ICON-1 was safe and well tolerated, its biological activity was evident in a Phase I clinical trial ( Wells et al, 2018 ), and the results reported from a Phase II clinical trial (NCT02358889) with improved BCVA as the primary outcome showed that hl-con1 0.3 mg in combination with ranibizumab 0.5 mg did not surpass ranibizumab 0.5 mg monotherapy. Another phase II trial (NCT03452527) showed that the CNV size assessed by OCT angiography in the ICON-1 0.6 mg maintenance therapy group did not exceed that in the ICON-1 0.6 mg combination therapy group (with aflibercept 2 mg).…”
Section: Clinical Trials Of Therapies For Nvamdmentioning
confidence: 99%
“…Basically, it consists of two identical chains of proteins: human Factor VII (fVII) as the targeting domain and human immunoglobulin G1 Fc as the effector domain, functioning as binding to pathological vessels overexpressing tissue factor ( Bora et al, 2003 ; Tezel et al, 2007 ). Although intravitreous administration of a single 0.3 mg dose of ICON-1 was safe and well tolerated, its biological activity was evident in a Phase I clinical trial ( Wells et al, 2018 ), and the results reported from a Phase II clinical trial (NCT02358889) with improved BCVA as the primary outcome showed that hl-con1 0.3 mg in combination with ranibizumab 0.5 mg did not surpass ranibizumab 0.5 mg monotherapy. Another phase II trial (NCT03452527) showed that the CNV size assessed by OCT angiography in the ICON-1 0.6 mg maintenance therapy group did not exceed that in the ICON-1 0.6 mg combination therapy group (with aflibercept 2 mg).…”
Section: Clinical Trials Of Therapies For Nvamdmentioning
confidence: 99%
“…A phase 1 multi-center dose escalation trial NCT03452527 evaluated intravitreal injection of ICON-1 in patients with CNV due to nAMD. Primary endpoints of safety and tolerability were met with no reported serious side effects [ 107 ]. EMERGE-2 is a phase 2 trial in which patients were randomized to receive either 0.5 mg ranibizumab and 0.3 mg of ICON-1, 0.5 mg of ranibizumab only, or 0.3 mg of ICON-1 only.…”
Section: Icon-1mentioning
confidence: 99%
“…Additionally, this therapy can be used in combination with other anti-VEGF medications. ICON-1 has been evaluated in a phase I, open-label trial in 18 patients with neovascular AMD, and met the primary endpoints of safety [ 57 ]. Further investigation of ICON-1 have been undertaken with EMERGE, a phase II, randomized, double-masked study in 88 patients with CNV in neovascular AMD.…”
Section: Drugs In the Pipelinementioning
confidence: 99%